Role of ethnicity and socioeconomic status (SES) in the presentation of retinoblastoma: findings from the UK. Issue 1 (15th May 2020) - Bourkiza, Rabia; Cumberland, Phillippa; Fabian, Ido Didi; Abeysekera, Hiranya; Parulekar, Manoj; Sagoo, Mandeep S; Rahi, Jugnoo; Reddy, M Ashwin
Abstract : Background: The relationship between the ethnic background or socioeconomic status (SES) and late retinoblastoma (Rb) presentation in the UK is unclear. We aimed to investigate if such correlations exist in a cohort of non-familial Rb cases. Methods: A cross-sectional study based at the two centres providing Rb care in the UK. Included were non-familial Rb cases that presented from January 2006 to December 2011. Epidemiological and clinical data were retrieved from medical charts, as well as patients' postcodes used to obtain the Index of Multiple Deprivation (IMD) score. A postal questionnaire was sent to participants' parents to collect further, person-level, information on languages spoken and household socioeconomic position. Statistical correlations to advanced Rb at presentation as well as to treatment by enucleation and need for adjuvant chemotherapy were investigated. Results: The cohort included 189 cases, 98 (51.8%) of which were males. The median age at diagnosis was 16 months (IQR 8–34 months). Of the study patients, 153 (81%) presented with advanced Rb; 78 (41%) with group D and 75 (40%) with group E Rb. A total of 134 (72%) patients were treated with enucleation. South Asian ethnicity and being in the most deprived IMD quintile were associated with a higher likelihood of presentation with advanced disease, but these estimates did not reach statistical significance. Older age at presentation was associated with enucleation and bilateral disease with adjuvant chemotherapy. Conclusions: In this national UK study of patients with non-familial Rb, there was no evidence of an association of ethnicity or SES and the risk of presenting with advanced disease. These findings may reflect equality in access of healthcare in the UK.